Lenalidomide maintenance for diffuse large B‐cell lymphoma patients responding to R‐CHOP: quality of life, dosing, and safety results from the randomised controlled REMARC study. (8th November 2019) - Thieblemont, Catherine; Howlett, Susannah; Casasnovas, René‐Olivier; Mounier, Nicolas; Perrot, Aurore; Morschhauser, Franck; Fruchart, Christophe; Daguindau, Nicolas; van Eygen, Koen; Obéric, Lucie; Bouabdallah, Reda; Pica, Gian Matteo; et al.
Summary: Lenalidomide maintenance therapy prolonged progression‐free survival (PFS) versus placebo in elderly patients with diffuse large B‐cell lymphoma (DLBCL) responding to induction chemotherapy in the phase 3 REMARC study. This subpopulation analysis assessed the impact of lenalidomide maintenance and treatment‐emergent adverse events (TEAEs) on health‐related quality of life (HRQOL). Global health status (GHS), and physical functioning and fatigue subscales were evaluated in patients who completed the European Organisation for Research and Treatment of Cancer quality‐of‐life questionnaire‐C30 v3.0. The impact of TEAEs classified post hoc as subjective (patients can feel) or observable (only measurable by physicians) on dose reductions and discontinuations was assessed. Among 457 patients (lenalidomide, n = 229; placebo, n = 228), mean (standard deviation) GHS was similar between treatment arms [68·2 (20·7) Versus 72·0 (17·8)] at randomisation and remained similar during maintenance. Patients receiving lenalidomide experienced no meaningful changes in GHS, physical functioning, or fatigue. Observable TEAEs were more common (81·1% Versus 66·3%) and more likely to lead to dose reductions, than subjective TEAEs in both arms. PFS was superior in the lenalidomide arm regardless of dose reduction. Lenalidomide maintenance prolonged PFS and did not negatively impact HRQOL in patients with DLBCL despite TEAEs being more common, when compared with placebo.